Answer:
![cos^2\theta + sin^2\theta = 1](https://tex.z-dn.net/?f=cos%5E2%5Ctheta%20%2B%20sin%5E2%5Ctheta%20%3D%201)
Step-by-step explanation:
Given
![(\frac{b}{r})^2 + (\frac{a}{r})^2](https://tex.z-dn.net/?f=%28%5Cfrac%7Bb%7D%7Br%7D%29%5E2%20%20%2B%20%28%5Cfrac%7Ba%7D%7Br%7D%29%5E2)
Required
Use the expression to prove a trigonometry identity
The given expression is not complete until it is written as:
![(\frac{b}{r})^2 + (\frac{a}{r})^2 = (\frac{r}{r})^2](https://tex.z-dn.net/?f=%28%5Cfrac%7Bb%7D%7Br%7D%29%5E2%20%20%2B%20%28%5Cfrac%7Ba%7D%7Br%7D%29%5E2%20%20%3D%20%28%5Cfrac%7Br%7D%7Br%7D%29%5E2)
Going by the Pythagoras theorem, we can assume the following.
- a = Opposite
- b = Adjacent
- r = Hypothenuse
So, we have:
![Sin\theta = \frac{a}{r}](https://tex.z-dn.net/?f=Sin%5Ctheta%20%3D%20%5Cfrac%7Ba%7D%7Br%7D)
![Cos\theta = \frac{b}{r}](https://tex.z-dn.net/?f=Cos%5Ctheta%20%3D%20%5Cfrac%7Bb%7D%7Br%7D)
Having said that:
The expression can be further simplified as:
![(\frac{b}{r})^2 + (\frac{a}{r})^2 = 1](https://tex.z-dn.net/?f=%28%5Cfrac%7Bb%7D%7Br%7D%29%5E2%20%20%2B%20%28%5Cfrac%7Ba%7D%7Br%7D%29%5E2%20%20%3D%201)
Substitute values for sin and cos
becomes
![cos^2\theta + sin^2\theta = 1](https://tex.z-dn.net/?f=cos%5E2%5Ctheta%20%2B%20sin%5E2%5Ctheta%20%3D%201)
280
The 0 is in the ones.
The 8 is in the tens.
The 2 is in the hundreds.
(2√5 + 3(√7))^2
(2√5 + 3(√7))(2√5 + 3(√7))
4*5 + 6√35 + 6√35 + 9*7
20 + 12√35 + 63
20 + 63 + 12√35
83 + 12√35
Answer:
u=11
Step-by-step explanation:
1. 36=47-9
36≠38
2. 36=47-11
36=36
3. 36=47-8
36≠39
4. 36=47-38
36≠9
Distributive property to become (2x+14)+3x=12